(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
Today, the concept of modern education is that the student should learn by himself. The teacher’s role is to manage his teaching, that is, to stimulate, organize, activate, coordinate and advise his activities. One of the main tasks of the concept of modernization of education of the Republic of Uzbekistan is the formation of a creative personality